2018
DOI: 10.1002/cem.3087
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiments: A comparison study from the non‐expert user's perspective

Abstract: In a digital era where terabytes of structured and unstructured records are created and stored every minute, the importance of collecting small amounts of high quality data is often undervalued. However, this activity plays a critical role in industrial and laboratory settings, when addressing problems from process modeling and analysis, to optimization and robust design. Implementing a screening design is usually the way to begin a systematic statistical Design of Experiments program. Its aim is to find the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Depending on the design’s geometry, certain factor combinations are required or evaded. There is a wide range of viable RSM designs with various geometries, each one offering certain assets as well as challenges [ 41 ]. The RSM of our choice was a FC-CCD, which allows for great prediction accuracy whilst examining each factor at three levels only.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the design’s geometry, certain factor combinations are required or evaded. There is a wide range of viable RSM designs with various geometries, each one offering certain assets as well as challenges [ 41 ]. The RSM of our choice was a FC-CCD, which allows for great prediction accuracy whilst examining each factor at three levels only.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, notice that no design can provide in one shot what is expected to be done through a sequential (screening-characterization-optimization) experimentation approach. For further guidelines and discussion on experimental design selection at various experimental stages in the response surface methodology framework, namely, when constraints exist, the reader is also referred to [39,[48][49][50][51][52][53][54][55]. To deal with multiobjective when constructing a design, the reader is referred to Lu et al [56].…”
Section: Doe-experimental Design Selection and Results Analysis Methodsmentioning
confidence: 99%
“…The presented research on lipid-based nanocarriers has also shown that one optimisation problem can be approached following different experimental designs, still arriving, in any case, at valid polynomials [97]. For instance, the same formulation problem regarding solid lipid nanoparticles has been optimised by a three-level full factorial, central composite, Box-Behnken or Taguchi designs [120,125,134,155].…”
Section: Discussionmentioning
confidence: 99%
“…Optimisation experimental designs are also known as response surface methodologies (RSM) and create higher-order model equations that maximise product similarity to the desired CQAs. Therefore, it is important to select a low number of factors under study, so the optimisation step maintains an affordable experimental workload [ 96 , 97 ]. However, recent research in the field has resulted in the appearance of the so-called definitive screening designs, which are able, under specific circumstances, to identify active quadratic terms with minimal experimental workload [ 98 ].…”
Section: Optimising the Outcomes: Statistical Design Of Experiments (Doe)mentioning
confidence: 99%